To solve for x in the equation 7(x+2)=-35, we first distribute the 7 to the terms within the parenthesis:
7*x + 7*2 = -35
This simplifies to:
7x + 14 = -35
Next, we isolate the term containing x by subtracting 14 from both sides of the equation:
7x = -49
Finally, we solve for x by dividing both sides of the equation by 7:
x = -49/7
Simplifying the division, we get:
x = -7
Therefore, the value of x that solves the equation 7(x+2)=-35 is x = -7.
Solve for x:
7(x+2)=-35
(5 points)
Group of answer choices
x = 10
x = -7
x = 3
x = 4.7
1 answer